2012
DOI: 10.1089/jwh.2011.3002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Desire Problems in Women Seeking Healthcare: A Novel Study Design for Ascertaining Prevalence of Hypoactive Sexual Desire Disorder in Clinic-Based Samples of U.S. Women

Abstract: In this sample of women recruited in the clinical care setting, we observed an overall prevalence rate of 7.4% of acquired, generalized HSDD, with markedly increased prevalence in midlife women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
1
18
1
3
Order By: Relevance
“…Rosen et al (2012) clinical sites by using FSFI, and reported its resulting sexual desire score of 1.9 from women with HSDD, which was showed to be similar to the sexual desire functioning in the present study's samples' score of 1.99.…”
Section: ⅳ Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Rosen et al (2012) clinical sites by using FSFI, and reported its resulting sexual desire score of 1.9 from women with HSDD, which was showed to be similar to the sexual desire functioning in the present study's samples' score of 1.99.…”
Section: ⅳ Discussionsupporting
confidence: 75%
“…However, since the participants in the study mentioned above were younger than those of the present study with the average age of 45.6 years, we think their sexual function score was reported lower. When the participants' sexual desire score of the present research is compared with that of other researches with similar sample ages, Rosen et al (2012) measured the degree of sexual function in women with HSDD (mean age 46.7) and reported a sexual function score of 15.4, which is higher than the score of 14.7 in our study. Kim & Lee (2010) reported that, with a mean sexual function score of 20.6, 57.5% of married women complained of sexual dysfunction.…”
Section: ⅳ Discussioncontrasting
confidence: 53%
“…Hypoactive sexual desire disorder (HSDD) is a common sexual dysfunction disorder, affecting up to 10% of women in the United States, [1][2][3] with similar prevalence worldwide. [4][5][6] HSDD is characterized by low sexual desire and associated distress.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The campaign fails to provide such information in many areas: (1) the treatment is falsely claimed to be as safe and effective as the treatments for males; (2) women are suggested as suffering from a medical condition with an identifiable biological background. As we demonstrated, this can at most be treated as one hypothetical factor among many others, while health-related or stress-related, psychological and relational factors are proven to be responsible for diminished sexual desire and accompanied distress in the majority of women;10 (3) the data about the other factors are not enumerated; (4) as a result, the availability of alternative, potentially effective and less intrusive treatments is not presented.…”
Section: The Campaignmentioning
confidence: 99%